Hypoglycorrhachia in adults with community-acquired meningitis: etiologies and prognostic significance. (October 2015) - Shrikanth, Vandana; Salazar, Lucrecia; Khoury, Nabil; Wootton, Susan; Hasbun, Rodrigo
Highlights: Hypoglycorrhachia in meningitis has significant clinical and prognostic significance. A concomitant cerebrospinal fluid and serum glucose determination is rarely done appropriately. The degree of hypoglycorrhachia may aid in the differential diagnosis. Summary: Objectives: Hypoglycorrhachia (cerebrospinal fluid (CSF) glucose <45 mg/dl) has been identified as a prognostic factor in patients with meningitis. The differential diagnosis of hypoglycorrhachia and its clinical significance was analyzed in the present study. Methods: This was a retrospective study of 620 adult patients with community-acquired meningitis (CSF white blood cell count >5 × 10 6 cells/l and absence of a CSF shunt or recent neurosurgical procedure (<1 month)) at eight Memorial Hermann hospitals in Houston, Texas, from January 2005 to December 2010. An adverse clinical outcome was defined as a Glasgow outcome scale score of ≤4. Results: Out of 620 patients with meningitis, 116 (19%) had hypoglycorrhachia. Etiologies of hypoglycorrhachia were idiopathic ( n  = 40), bacterial ( n  = 27), cryptococcal ( n  = 26), viral ( n  = 15), and tuberculous ( n  = 4). Patients with hypoglycorrhachia were more likely to be immunosuppressed, have a history of intravenous drug use, and present with a vesicular or petechial rash, nausea or vomiting, nuchal rigidity, sinusitis/otitis, abnormal mental status, and focal neurological deficits compared to those patients without hypoglycorrhachia ( p  < 0.05). Additionally, patients in the hypoglycorrhachia group had significantly higher rates of positive CSF and blood cultures, urgent treatable conditions, and abnormal cranial imaging ( p  < 0.05). Furthermore, patients with hypoglycorrhachia had more adverse clinical outcomes (26/116 (22.4%) vs. 45/504 (8.9%); p  < 0.001). Conclusion: Hypoglycorrhachia has significant clinical and prognostic value in the evaluation of adult patients with community-acquired meningitis.